Ligand cross-feeding resolves bacterial vitamin B12 auxotrophies - Wienhausen, Gerrit; Moraru, Cristina; Bruns, Stefan; Tran, Den Quoc; Sultana, Sabiha; Wilkes, Heinz; Dlugosch, Leon; Azam, Farooq; Simon, Meinhard (Nature (London), 2024)
Cobalamin (vitamin B 12 , herein referred to as B 12 ) is an essential cofactor for most marine prokaryotes and eukaryotes 1 , 2 . Synthesized by a limited number of prokaryotes, its scarcity affects microbial interactions and community dynamics 2 – 4 . Here we show that two bacterial B 12 auxotrophs can salvage different B 12 building blocks and cooperate to synthesize B 12 . A Colwellia sp. synthesizes and releases the activated lower ligand α-ribazole, which is used by another B 12 auxotroph, a Roseovarius sp., to produce the corrin ring and synthesize B 12 . Release of B 12 by Roseovarius sp. happens only in co-culture with Colwellia sp. and only coincidently with the induction of a prophage encoded in Roseovarius sp. Subsequent growth of Colwellia sp. in these conditions may be due to the provision of B 12 by lysed cells of Roseovarius sp. Further evidence is required to support a causative role for prophage induction in the release of B 12 . These complex microbial interactions of ligand cross-feeding and joint B 12 biosynthesis seem to be widespread in marine pelagic ecosystems. In the western and northern tropical Atlantic Ocean, bacteria predicted to be capable of salvaging cobinamide and synthesizing only the activated lower ligand outnumber B 12 producers. These findings add new players to our understanding of B 12 supply to auxotrophic microorganisms in the ocean and possibly in other ecosystems. Two species of auxotrophic marine bacteria are shown to share precursors to synthesize the essential cofactor vitamin B 12 , and such ligand cross-feeding may be a common phenomenon in the ocean and other ecosystems.